Synthesizing Effective Instructional Strategies for Enhancing Speaking Skills in Primary Education: A Qualitative Meta-Synthesis of 34 Empirical Studies - Harahap, Syawal Fitrah; Ikawati, Erna (Jurnal Hata Poda, 2025)
This study synthesizes effective instructional strategies for enhancing speaking skills among primary school learners through a qualitative meta-synthesis of thirty-four empirical studies. The analysis examines convergent findings across communicative, narrative, multimodal, collaborative, and formative approaches to identify core mechanisms supporting oral language development. Results indicate that meaningful communicative interaction, structured narrative organization, multimodal reinforcement, peer-based collaboration, and continuous formative feedback collectively contribute to substantial improvements in fluency, coherence, and expressive clarity. The cross-method consistency suggests that speaking proficiency emerges not from isolated techniques but from the interplay of cognitive, affective, and social learning processes. The resulting conceptual model offers an integrated framework for teachers to design holistic speaking instruction. Practically, this study highlights the importance of interactive, multimodal, and collaborative strategies in strengthening communication competence in primary education.